Development and Validation of a 7-Gene Inflammatory Signature Forecasts Prognosis and Diverse Immune Landscape in Lung Adenocarcinoma - Nai, Aitao; Ma, Feng; He, Zirui; Zeng, Shuwen; Bashir, Shoaib; Song, Jian; Xu, Meng (Frontiers in Molecular Biosciences, 2022)
Background: Inflammatory responses are strongly linked with tumorigenesis and cancer development. This research aimed to construct and validate a novel inflammation response-related risk predictive signature for forecasting the prognosis of patients with LUAD. Methods: Differential expression analysis, univariate Cox, LASSO, and multivariate Cox regression analyses of 200 inflammatory response-related genes (IRRGs) were performed to establish a risk predictive model in the TCGA training cohort. The performance of the IRRGs model was verified in 8 GEO datasets. GSEA analysis, ESTIMATE algorithms, and ssGSEA analysis were applied to elucidate the possible mechanisms. Furthermore, the relationship analysis between risk score, model genes, and chemosensitivity was performed. Lastly, we verified the protein expression of 7 model genes by immunohistochemical staining or Western blotting. Results: We constructed a novel inflammatory response-related 7-genes signature (MMP14, BTG2, LAMP3, CCL20, TLR2, IL7R and PCDH7). Patients in the high-risk group presented markedly decreased survival time in the TCGA cohort and 8 GEO cohort than the low-risk group. Interestingly, multiple pathways related to immune response were suppressed in high-risk groups. The low infiltration levels of B cell, dendritic cell, natural killer cell, and eosinophil can significantly affect the unsatisfactory prognostic of the high-risk group in LUAD. Moreover, the tumor cells' sensitivity to anti-cancer drugs was markedly related to risk scores and model genes. The protein expression of 7 model genes was consistent with the mRNA expression. Conclusion: Our IRRGs prognostic model can effectively forecast LUAD prognosis and is tightly related to immune infiltration.